Enhancing intercultural communication via the ENACT Web App in language teaching - Belma Haznedar; Elifcan Öztekin; Sumru Akcan (Literacy Trek)
Digital language learning provides an immersive context for language learners to engage in intercultural communication (Liaw, 2019; Dooly & Vinagre, 2021). This study investigates the impact of a digital tool, the ENACT web app (Communities, Languages, and Activities), on intercultural language learning from the pre-service English language teachers’ perspective. The ENACT web app, which embraces the intercultural, digital, and communication skills of language learners, aims to develop the intercultural awareness and understanding of language learners through two-way knowledge-generating task-based activities. Ten pre-service English language teachers, who participated in the project as workshop facilitators, were initially engaged with the web app as users by completing a 2-week online training. After the training, they facilitated intercultural pairs in producing cultural activities in a task-based digital learning pedagogy in 3-5 hour sessions. They also completed final reflection papers at the end of the entire project engagement as a culminating product. To this end, this study presents mixed-method research with quantitative survey data and qualitative reflections of the pre-service teachers: (1) descriptive scores from pre and post-training responses to digital skills assessment and cultural awareness questionnaires, (2) reflective answers to open-ended questions about their gains in the e-portfolio in the middle and end of the online training, and (3) final reflection papers on intercultural understanding after the facilitation of the workshops. The survey findings showed that the pre-service teachers increased their cultural and digital knowledge through digital materials on the web platform. The thematic analysis of the reflections also indicated that they found the use of the task-based language teaching methodology effective in offering an interactive learning experience and enhancing learner involvement. The study suggests that integrating cultural tasks into the curriculum for language learning offers real-life learning experiences and contributes to both the language and content knowledge of the students.